Aplicação do método de Taguchi em instituição pública - Toto, Lélia Lage (2001)
Taguchi's Method is very well known in the industrial sector of manufacturing in the quality control. This method has interesting concepts such as, robustness and loss of quality, what make it very useful to identify variation in the production system, quantifying the variation and allowing eliminating the undesirable factors. Reviewing the literature we verify that the Taguchi's Method were never applied in the organization environment, as a tool to quantify and make hierarchical classification of the management problems. We decide to make an experiment and use the Taguchis Method at Instituto de Saúde. Through the use of orthogonal matrix it was possible to quantify the dissatisfaction concerning the management problems and list them in a priority order to later resolution. The method was validated with verification of the results through interviews done after the process that showed big concordance with the previous results. Our conclusion is that Taguchi's Method could be very useful in organizations, mainly when a lot of variables are involved. This method is good to reduce the number of factors that at the beginning of a reorganization process seems equally important. The construction of a priority scale is without doubt, important to the management team, who will be able to take efficient decisions.